Significance and Prospect of Brf1 Overexpression - Zheng, Liling; Lin, Yongluan; Hong, Zaifa; Shen, Dongyan; Zhong, Shuping (Archives of Pharmacy and Pharmaceutical Sciences, 2023)
Brf1 (TFIIB-related factor 1) is a transcription factor, which specifically modulates the transcription of RNA polymerase III-dependent genes (RNA Pol III genes), such as tRNAs and 5S rRNA. The products of tRNAs and 5S rRNA transcription will be changed with the alteration of Brf1 expression. Whereas deregulation of Brf1 and RNA Pol III genes are tightly associated with cell proliferation and transformation, and tumorigenesis. In recent years, emerging studies indicate that Brf1 expression is increased in patients with cancers. In this review, we summarize the progress of the abnormal expression of Brf1 in different human cancers to explore an underlying mechanism and its clinical implication, as well as to prompt its application prospect. With the depth of the Brf1 study and the progress of biotechnology, the status of Brf1 expression may be used as a universal indicator of the early detection and prognosis observation of human cancers.